Biodiversity in the Sustainable Development Goals - Corina Dinculescu (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
Biodiversity is influenced by the process of economic development, between the two there is a causal relationship - when development does not respect the environment, biodiversity experiences negative transformations. The EU Biodiversity Strategy 2030, which derives from the 2030 Agenda for Sustainable Development, calls for member states to step up their conservation efforts to protect 30% of Europe's land and marine area by 2030 (of which 10% will have to be strictly protected). Although Europe already has more protected areas than any other continent (mainly through the Natura 2000 Network) and among the highest proportions of its area covered by protected areas, the current network of protected sites is not large enough to protect biodiversity. This paper proposes an analysis of the significant aspects of biodiversity in Romania, based on statistical data, in the context of the sustainable development goals. Evaluating public data sources, national concerns in the field of environmental protection, respectively biodiversity, are highlighted, through the analysis of specific indicators, through which the progress made in achieving the goals of the 2030 Agenda is evaluated: protected areas, conservation and protection of wetlands, mountain ecosystems, sustainable forest management, transition to circular economy, relation with agriculture - influences and consequences, all in a statistical approach, at national level (without neglecting, however, the European context).
Keywords: P48; Q01; Q15; Q56; Q57; 330; environmental protection; biodiversity; protected areas